Studi Komparasi Antara Strategi Learning Start WithA Question Dengan Strategi Everyone Is A TeacherHere Terhadap Hasil Belajar IPS Siswa Kelas IVMim PK Kartasura Tahun Ajaran 2015/2016 - Oktavia Putri, Ardwiyan; , Dra. Ratnasari Diah Utami, M. Si (2016)
This research aim to determine: (1) differences in the use of Learning Start With a Question Strategy to the Everyone Is a Teacher Here Strategy on learning outcomes of Social Science Education at the grade 4th students of MIM PK Kartasura at 2015/2016, (2) better implementation of Learning Start With a Question Strategy to the Everyone Is a Teacher Here Strategy on learning outcomes of Social Science Education at grade 4th students of MIM PK Kartasura at 2015/2016. This research is quantitative experiment. The subject of this reearch are students 4th grade A and 4th grade B of MIM PK Kartasura. The technique of data collection use test, documentary, and interview. The instruments test include test the validity and reliability testing. The technique of analizing data is t-test which doing pre-requisite test like homogenity test and normality test first. Based on the data analysis about 5% degree's significance the resulr shows ttest > ttable is 2,375 > 2,001 which the average of the learning outcomes of Social Science Education at 4th grade A is higher than 4th grade B, is 84 > 82,06. The conclusion is (1) there are differences in learning outcomes of Social Science Education using Learning Start With a Question Strategy and Everyone Is a Teacher Here Strategy at the grade 4th students of MIM PK Kartasura at 2015/2016. (2) Everyone Is a Teacher Here Strategy is bigger than Learning Start With a Question Strategy in learning outcomes of Social Science Education at 4th grade students of MIM PK Kartasura at 2015/2016. Keyword: learning start with a question strategy, everyone is a teacher here strategy, learning outcomes.